International Transmission of Stock Market Movements - Eun, Cheol S.; Shim, Sangdal (Journal of Financial and Quantitative Analysis, 1989)
This paper investigates the international transmission mechanism of stock market movements by estimating a nine-market vector autoregression (VAR) system. Using simulated responses of the estimated VAR system, we (i) locate all the main channels of interactions among national stock markets, and (ii) trace out the dynamic responses of one market to innovations in another. Generally speaking, a substantial amount of multi-lateral interaction is detected among national stock markets. Innovations in the U.S. are rapidly transmitted to other markets in a clearly recognizable fashion, whereas no single foreign market can significantly explain the U.S. market movements. Also, the dynamic response pattern is found to be generally consistent with the notion of informationally efficient international stock markets.